2017
DOI: 10.1007/s00167-017-4710-8
|View full text |Cite
|
Sign up to set email alerts
|

In Achilles tendinopathy, the neovascularization, detected by contrast-enhanced ultrasound (CEUS), is abundant but not related to symptoms

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
0
33
1
3
Order By: Relevance
“…Low baseline blood flow and blood velocity in healthy Achilles tendon makes CDUS and PDUS evaluation difficult . Contrast‐enhanced US improves the visualization of neovascularization in the Achilles tendon midportion, but its applicability in healthy controls is not well established . Note that the interpretation of US‐based measurements is subjective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low baseline blood flow and blood velocity in healthy Achilles tendon makes CDUS and PDUS evaluation difficult . Contrast‐enhanced US improves the visualization of neovascularization in the Achilles tendon midportion, but its applicability in healthy controls is not well established . Note that the interpretation of US‐based measurements is subjective.…”
mentioning
confidence: 99%
“…6,12,13 Contrast-enhanced US improves the visualization of neovascularization in the Achilles tendon midportion, but its applicability in healthy controls is not well established. 14 Note that the interpretation of US-based measurements is subjective. Thus, there is a high clinical urgency to develop robust, noninvasive, and quantitative techniques to assess intratendinous microcirculation, ie, blood volume and blood flow, in human Achilles tendon.…”
mentioning
confidence: 99%
“…Additionally, Genovese et al 34 and De Marchi et al 35 were able to demonstrate the superiority of DCE‐US in detection of neovessels and neovascularization compared to power Doppler US in tendon tissues. Due to the overall strong correlation in this study, we can assume that DCE‐US and DCE‐MRI are feasible methods for assessment of neovascularization during tendon regeneration, whereas DCE‐US may more accurately identify changes in microperfusion over time.…”
Section: Discussionmentioning
confidence: 97%
“…A study using an in vivo murine model showed that this supporting neovasculature originates by sprouting larger host tissue‐derived blood vessels that run parallel to peripheral nerves . This is a significant insight in the context of tendinopathy where neovascularization appears as ingrowths from the surrounding paratendon . The angiogenic proliferation required to support adipose tissue expansion appears to be mediated by VEGF, with VEGF‐A believed to play the most important role.…”
Section: Tendinopathymentioning
confidence: 99%